Evaluasi Implementasi Pembelajaran Daring pada Pembelajaran Akuntansi Perusahaan Dagang di Masa Pandemi Covid-19 - Jesica Emilia; Bambang Ismanto; Dwi Iga Luhsasi (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to evaluate online learning in trading company accounting learning in class XI Accounting students during the Covid-19 pandemic. The research used a qualitative approach with Kirkpatrick's evaluation model. The subjects in this study were trading company accounting teachers and students of class XI Accounting at SMK Negeri 1 Banyudono. Data collection techniques were through observation, interviews, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing. The results showed that the reaction of online learning in accounting trading company class XI Accounting students and teachers were less satisfied in carrying out online learning activities, but students were quite satisfied with the available facilities and the motivation provided by the teacher. The learning process of trading company accounting students experienced an increase in knowledge, skills, and changes in attitude, but not as a whole. Changes in student behaviour occured somewhat after online learning of trading company accounting, but not completely. Student learning outcomes obtained online were good but not as good as when face-to-face learning was carried out. In conclusion, online learning for trading company accounting lessons for class XI Accounting during the Covid-19 pandemic is quite effective.